Elements of information theory - Cover, T. M. (Wiley-Interscience, 2006)
Suitable for use in advanced undergraduate and graduate courses in electrical engineering, statistics, and telecommunications, this textbook covers the basics of information theory. Topics include (for example) entropy, data compression, channel capacity, rate distortion, network information theory, and hypothesis testing. The second edition features new material on source coding, portfolio theory, and feedback capacity, as well as 200 new problems.